2013
DOI: 10.1016/s1001-0742(12)60123-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airflow on biodrying of gardening wastes in reactors

Abstract: Biodrying consists of reducing moisture by using the heat from aerobic bio-degradation. The parameters that control the process are: aeration, temperature during the process, initial moisture of biowaste, and temperature and relative humidity of the input air. Lawn mowing and garden waste from the gardens of the University Jaume I, Castellón (Spain) were used as a substrate. Biodrying was performed in 10 reactors with known air volumes from 0.88 to 6.42 L/(min·kg dry weight (dw)). To promote aeration, 5 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 29 publications
(52 reference statements)
4
17
3
2
Order By: Relevance
“…The calorific values of the fuel in bioreactors K4 and K5 increased by 3.1 and 2.7 MJ·kg -1 , respectively. Similar effects (in terms of weight loss, moisture content and increase in calorific value) were achieved in the work of Colomer-Mendoza et al [44], Ma et al [45], Tom et al [6] and Mohammed et al [46]. The lack of aeration in the K6 bioreactor resulted in a reduction in fuel quality.…”
Section: Resultssupporting
confidence: 72%
“…The calorific values of the fuel in bioreactors K4 and K5 increased by 3.1 and 2.7 MJ·kg -1 , respectively. Similar effects (in terms of weight loss, moisture content and increase in calorific value) were achieved in the work of Colomer-Mendoza et al [44], Ma et al [45], Tom et al [6] and Mohammed et al [46]. The lack of aeration in the K6 bioreactor resulted in a reduction in fuel quality.…”
Section: Resultssupporting
confidence: 72%
“…Cai et al (2013) showed that forced aeration controlled the pile temperature and improved evaporation, making it the key factor influencing water loss during the process of sewage sludge biodrying. Colomer-Mendoza et al (2013) studied the effect of AFR on the biodrying of gardening wastes, showing that high airflow affects the biodrying process, because the thermophilic phase is avoided, so that the waste is dried only by physical phenomena and not by biodrying. Finally, Sharara et al (2012) showed that high aeration level was superior in terms of both drying energy and time requirements than the other considered rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is an established fact that combustible non-biogenic materials are characterized by higher heat content per unit weight than combustible biogenic materials. Consequently, the ratio of biogenic to non-biogenic material proportion can have a considerable effect on the heat content of a waste material intended for combustion purpose [40,49]. Figure 1 shows the relationship between moisture content and calorific value.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study to investigate the effect of air-flow on the bio-drying of gardening wastes, it was found that higher air-flow rate corresponds to greater weight loss (40-57% weight loss) and leachate production at low air-flow. Even though higher air-flow rate causes higher water removal, it was further stressed that it is imperative to identify the optimal air-flow rate for bio-drying, since excessively high air-flow rate may induces physical drying [40]. It is shown that forced aeration during sewage sludge bio-drying controlled the matrix temperature and improved evaporation, establishing it as a vital parameter influencing water loss [18].…”
Section: Air-flow Ratementioning
confidence: 99%
See 1 more Smart Citation